2008
DOI: 10.1590/s0104-56872008000100010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização das alterações de linguagem em crianças com histórico de intoxicação por chumbo

Abstract: Background: lead poisoning can have a negative impact on the neuropsychological functions, including language, due to the damage it causes to the development of the Central Nervous System. Aim: to verify the occurrence of language disorders in children who suffered from led poisoning and to verify the correlation between the lead concentration level in the blood and the language disorders presented by the children. Method: language evaluation of 20 preschoolers, with lead concentration level in the blood above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
3
0
3
Order By: Relevance
“…Although few studies have specifically examined children with language impairment for EBL, work by Gahyva, Crenitte, Galdana, & Hage in 2008 pointed clearly to the multifactored involvement of environmental and genetic factors in language impairment. In their sample of 20 preschoolers with blood lead levels > 10μg/dL, 65% (n=13) of the children had language impairments including phonology and other language domains (Gahyva, Crenitte, Caldana, & Hage, 2008). Interestingly, a correlation was not found between the severity of language impairment and the degree of EBL.…”
Section: Introductionmentioning
confidence: 99%
“…Although few studies have specifically examined children with language impairment for EBL, work by Gahyva, Crenitte, Galdana, & Hage in 2008 pointed clearly to the multifactored involvement of environmental and genetic factors in language impairment. In their sample of 20 preschoolers with blood lead levels > 10μg/dL, 65% (n=13) of the children had language impairments including phonology and other language domains (Gahyva, Crenitte, Caldana, & Hage, 2008). Interestingly, a correlation was not found between the severity of language impairment and the degree of EBL.…”
Section: Introductionmentioning
confidence: 99%
“…Segundo Mazoto et al, (2014), quanto maior a proximidade do local contaminado, maior a contaminação pelo chumbo. Quatro, dos seis estudos analisados (JORGE, 2008;GAHYVA, 2008;RODRIGUES, 2007;RODRIGUES, 2009), foram realizados com crianças entre 1 e 6 anos e encontraram defasagens na área de linguagem. É sabido que nos primeiros anos de vida ocorre a maturação do sistema nervoso com subsequente desenvolvimento de habilidades auditivas e de linguagem (FRIEDERICI, 2006).…”
Section: Resultsunclassified
“…A study that assessed 20 children with lead poisoning, aged three to six years, found immediate memory alteration in 65% of children 35 . When assessing 25 school-age children (six to thirteen years) through the Academic Performance Test, one study found better performance children not contaminated by lead and worse performance in children with lead poisoning 36 .…”
Section: Discussionmentioning
confidence: 99%